2014
DOI: 10.1186/preaccept-6069764581413424
|View full text |Cite
|
Sign up to set email alerts
|

Diminished transmission of drug resistant HIV-1 variants with reduced replication capacity in a human transmission model

Abstract: Background: Different patterns of drug resistance are observed in treated and therapy naïve HIV-1 infected populations. Especially the NRTI-related M184I/V variants, which are among the most frequently encountered mutations in treated patients, are underrepresented in the antiretroviral naïve population. M184I/V mutations are known to have a profound effect on viral replication and tend to revert over time in the new host. However it is debated whether a diminished transmission efficacy of HIV variants with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…It is now well established that M184V and M184I mutations occurring in the RT polymerase active site of HIV‐1 reduced its susceptibility to 3TC/FTC drugs. Whereas other mutations, such as M184L, M184T, or M184A, have been described and studied in vitro , there is still a lack of data that allow considering these variants as NRTI‐resistant mutants. In a large cohort of HIV‐1‐infected patients, we observed that M184L and M184T mutations occurred under and/or after NRTI treatment.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It is now well established that M184V and M184I mutations occurring in the RT polymerase active site of HIV‐1 reduced its susceptibility to 3TC/FTC drugs. Whereas other mutations, such as M184L, M184T, or M184A, have been described and studied in vitro , there is still a lack of data that allow considering these variants as NRTI‐resistant mutants. In a large cohort of HIV‐1‐infected patients, we observed that M184L and M184T mutations occurred under and/or after NRTI treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Compared to the wild type (WT), M184V mutation confers a reduced fitness, which may explain that the HIV‐1 reverts to wild type when NRTI treatment ceases . It has also been shown that this variant increases fidelity of HIV‐1 RT, thus reducing genetic diversification, one of key natural defensive mechanisms. M184I is considered as a transient variant since it appears early under 3TC‐based regimens and then disappears in favor of M184V mutant due to its lower fitness .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a skin model, drug-resistant variants with a low replicative capacity (M184V/I/T) were less 2015 able to infect primary Langerhans cells compared to resistant viruses with a higher replicative capacity (K103N) or wild-type virus. Subsequent transmission to target cells was also decreased in these resistant variants (Pingen et al 2014). This issue needs further study in the future.…”
Section: Transmissibility Of Resistant Virusmentioning
confidence: 95%